2017
DOI: 10.3345/kjp.2017.60.4.118
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tuberculosis treatment on leptin levels, weight gain, and percentage body fat in Indonesian children

Abstract: PurposeTuberculosis (TB) remains a problem in the community. TB patients usually experience malnutrition, which is characterized by both decreased body weight (BW) and body fat percentage (BFP). Leptin, an important regulator of BW, also plays an important role in cellular immunity, which is integral to defense against Mycobacterium tuberculosis infection. We analyzed the effect of an anti-TB treatment regimen on the leptin level, BW, and BFP of children with TB.MethodsThe design of this study was a group inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 23 publications
2
11
0
1
Order By: Relevance
“…Similarly, previous reports have also found that ATT is associated with increased systemic levels of leptin in PTB individuals. [26][27][28] Our data confirmed and extended these results and demonstrated that successful completion of ATT (and consequent cure of TB) was associated with elevated levels of leptin.…”
Section: Discussionsupporting
confidence: 82%
“…Similarly, previous reports have also found that ATT is associated with increased systemic levels of leptin in PTB individuals. [26][27][28] Our data confirmed and extended these results and demonstrated that successful completion of ATT (and consequent cure of TB) was associated with elevated levels of leptin.…”
Section: Discussionsupporting
confidence: 82%
“…29 Maxitalia et al reported that the body weight, body fat percentage, and leptin levels were significantly increased at the end of treatment in TB patients that had presented with mild chronic malnutrition at the time of diagnosis. 30 To the best of our knowledge, our study is the first to address malnutrition among pediatric TB cases in Turkey. In this study, although we observed clinical improvement at the end of treatment, mild or moderate malnutrition continued.…”
Section: Discussionmentioning
confidence: 93%
“…Leptin is thought to be a mediator in the complex process between TB, nutrition status and host immune response. Leptin level increment in the body is correlated to increment energy, protein and fat intake which is increased after administration of oral anti-tuberculosis therapy either in intensive phase or maintenance phase [8]. Thus, the more energy intake will increase body weight during and after tuberculosis therapy.…”
Section: Discussionmentioning
confidence: 99%